PRODUCT DEVELOPMENT STRATEGY FOR GERIATRIC SERVICES: A CASE STUDY AT A HOSPITAL IN SURABAYA - Anggreini, Narolitha; Hadinata, Immanuel Michael; Ernawaty, Ernawaty (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
To support customer needs and ensure smooth organizational operations, such as in hospitals, the development of service products is essential. This analysed strategies for service product development and design recommendations to enhance services and improve patient satisfaction. A descriptive observational study with a cross-sectional approach was conducted. The sample recruitment employed purposive sampling, with a total sample size of 210 patients. The independent variables were social, economic, technological, and policy factors, while the dependent variable was the strategy for service product development. The research instrument was a questionnaire designed and tested for validity and reliability by the researchers. Social factors showed that family support was low at 66.2%, knowledge of electronics and internet development was 73.8%, knowledge of geriatric services was 70.5%, physical quality was 72.8%, and hobbies were 85.3%, categorized as high. For economic factors, the recognition of needs was 80.5%, information-seeking was 75.8%, and purchasing decisions were 77.6%, all categorized as high. Several product opportunity gaps were identified from the analysis of social, economic, technological, and policy factors in the development of geriatric services. The development of day-care services and the implementation of Patient Service Representatives & Geriatric Hotline Services are significant recommendations to meet patient service needs.